ANALISIS PENGALAMAN GURU DALAM MENGELOLAH KONFLIK SISWA DI SD LABORATORIUM UNG KOTA GORONTALO - Dewi Suryani T. Hamzah; Hamid Isa; Yulanti S. Mooduto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to understand and describe in depth Teachers’ experience in managing student conflict at UNG Laboratory Elementary School, Gorontalo City”. This study aims to understand teachers’ experiences in depth regarding how they interpret, manage, and reflect on conflicts that occur in the learning process. This study uses a qualitative descriptive research type with a qualitative phenomenological approach. Data collection techniques include observation, interviews, documentation, and triangulation techniques to test data validity. The research subjects consisted of third-, fifth-, and sixth-grade teachers and the principal. The results show that teachers’ conflict management at UNG Laboratory Elementary School proceeds through four main experiences: preventive, curative, educative-emotional, and reflective. The findings of this study confirms that comprehensive conflict management contributes to a more positive learning anvironment and healthy relationships among students.